Diode 577-nm Laser Plus Tioconazole 28% Nail Solution versus Topical Tioconazole 28% Nail Solution Alone in Treatment of Onychomycosis - Sara Yossif; Hazem Abdel-Aleem; Khalid Tawfeek (International Journal of Medical Arts, 2023)
Background: Onychomycosis affecting 5.5% of the population worldwide which may be treated by medical antifungal therapy or laser therapy which is attractive to avoid side effects, prevent developing of microbial resistance and safe with no mutagenic or cytotoxic effect. Aim of the Work: To evaluate the efficacy and safety of diode 577-nm laser in the treatment of onychomycosis.Patients and Methods: This study involved 30 onychomycosis patients with 87 affected nails, everyone had two affected sites [finger nails/toe nails] then randomly allocated into two groups: group [A] in which one site was treated by diode laser [577-nm] plus Tioconazole 28% [Fungibacid 28% nail solution] nail solution while in group [B] the other site in the same patient was treated by Tioconazole 28% nail solution only. We assessed the improvement by Onychomycosis Severity Index [OSI], culture and patient satisfaction. Results: The OSI severity in Diode 577-nm + Tioconazole group decreased from 36.7% before treatment to 20% after 3 months an continue to decrease after 6 months to 3.3%. However, in Tioconazole only group, the severity still the same as before treatment 36.7% after 3 months while after 6 months decreased to 20%. There was a significant difference between patients with severe OSI score while no significant difference between patients with mild and moderate OSI score among both groups at the end of follow up. There were 2 [6.7%] patients after 3 months and 18 [60%] patients after 6 months have complete resolution in Diode 577-nm + Tioconazole group while in Tioconazole only group, no one has complete resolution after 3 months but after 6 months there were 11 [36.7%] patients have complete resolution with significant difference between both groups at 3 and 6 months [p < 0.001 & 0.046].Conclusion: The 577-nm diode yellow laser is an effective and safe option for the treatment of onychomycosis.